Dupuytren’s Contracture in Athletes: Prevalence, Causes, Treatment. A Literature Review and guide for sport professionals. - Antczak, Tomasz; Gajda-Bathelt , Monika; Dąbek, Monika; Jania, Katarzyna; Perlicka , Zuzanna; Smolińska , Karolina; Sadkowska , Paulina; Kulczycka , Julia; Popow , Weronika; Ciołkosz , Michał (Quality in Sport, 2025)
Background. Dupuytren’s contracture is a fibrotic condition of the hand, traditionally associated with age, genetics, and metabolic factors. However, recent observations suggest it may also appear in younger individuals with high physical activity levels. Aim. The aim of this study was to review the current literature on Dupuytren’s contracture in athletes and explore possible links between training load, mechanical stress, and early disease onset. Material and methods. The review was conducted using published case reports, observational studies, and athlete-specific data describing Dupuytren’s contracture symptoms, diagnosis, and treatment outcomes using a PubMed search and inclusion criteria. Results. Several studies describe early nodular changes and functional symptoms in athletes from sports such as climbing, judo, hockey, and rowing. Repetitive microtrauma, overuse, and delayed tissue recovery may contribute to earlier fibrotic changes. Functional impairment in athletes often appears earlier and requires tailored treatment to preserve performance. Conclusions. Dupuytren’s contracture in athletes may follow a distinct pathway, triggered or accelerated by mechanical overload. Early recognition and sport-specific management may help prevent long-term complications. Further studies are needed to identify risk factors and develop screening tools for athletic populations.